Secuencia de enseñanza sobre el electromagnetismo - Meneses Villagrá, Jesús Ángel; Caballero Sahelices, M. Concesa (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
In orden to plan the teaching sequence of any physical topic, weconsider essential to bear in mind three factors, at least: the scientific problems that arise from the subjects to be studied, the conceptions of the students to whom the teaching is addressed, and above all, the strategies and methodological process to be taken. This paper presents the didactic model, based on a constructivist approach, we use, the university students' conceptions about electromagnetism, the conceptual map where we make explicit our points of view of the concepts we work on, and the group activities we have designed in order to promote the conceptual, methodological and attitudinal change.